INOVASI PRODUK SEBAGAI MEDIASI PENGARUH ORIENTASI PASAR DAN ORIENTASI KEWIRAUSAHAAN TERHADAP KINERJA UMKM - Rahayu, Sri; Syafe’i, Darman; Dahlia, Dahlia; Wiranata, Hilmi; Sari, Palupi Indah (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2025)
The success of Micro, Small, and Medium Enterprises (MSMEs) in maintaining business sustainability largely depends on their ability to develop innovative strategies rooted in market orientation and entrepreneurial orientation. In South Sumatra, MSMEs are required to produce superior products with high competitiveness in order to survive in a dynamic and competitive market. This study aims to analyze the influence of market orientation and entrepreneurial orientation on product innovation; analyze the influence of market orientation, entrepreneurial orientation, and product innovation on MSME performance; and examine the mediating role of product innovation in the relationship between market orientation and entrepreneurial orientation on MSME performance in South Sumatra. This research employed a quantitative approach using a survey method. Data were collected through Google Forms from 100 MSME respondents across five cities in South Sumatra. Data were analyzed using multiple linear regression with the assistance of SPSS version 26. Hypothesis testing was conducted through t-tests, F-tests, and the measurement of the coefficient of determination (R²). The results show that market orientation and entrepreneurial orientation have a positive and significant influence on product innovation, with an F-value of 912.447 and R² of 0.950. Both market orientation and entrepreneurial orientation also significantly affect MSME performance, with an F-value of 708.659 and R² of 0.936. Furthermore, product innovation has a very significant impact on MSME performance, with an R² of 0.989. Product innovation also acts as a mediator that strengthens the influence of market orientation and entrepreneurial orientation on MSME performance. Market orientation and entrepreneurial orientation play a crucial role in driving product innovation, which in turn significantly impacts MSME performance. Product innovation is proven to be a strong mediating variable in this relationship. The practical implication of these findings is the need to strengthen strategic and innovative aspects to enhance the competitiveness and sustainability of MSMEs in South Sumatra.